Pengaruh Konsentrat yang Dicampur Tepung Silase Chromolaena Odorata, Analog Hidroksi Metionin, Minyak Nabati terhadap Komposisi Tubuh Ternak Sapi Bali - Oematan, Gustaf (Yayasan Sumber Daya Manusia Cerdas, 2026)
The study aims to find out, analyze and explain the influence of hydroxy methionine analogues, vegetable oil acids on the body composition of fattening male Balinese cattle. Using a Group Randomized Design (GRD) with four treatments and four tests. Sixteen heads of cattle with a weight range of 78-183 kg (average 130.5kg) with a CV of 25.33% were used as experimental units. The ration contains 18% protein and metabolic energy = 16 MJ/kg BK with a target weight gain of 0.6 kg/day. The ratio of concentrate administration is 2/3 part of the percentage of livestock needs (3% body weight) while rice straw and drinking water are provided ad libitum. Treatment as follows: RA = Concentrate + Rice Straw ad libitum (control); RB = RA + 3 g Hydroxy Methionine Analogue (AHM); RC = RA + 0.5% Vegetable Oil (MN) and RD = RA + 3 g AHM + 0.5% MN. The measured variables are the body composition of cattle (body urea, body protein, body fat, body water and body minerals). The results of the study of giving hay and concentrates containing Odorata without successive supplementation provided body composition: body water 53.16%; body protein 15.24%; body fat 12.13%; body minerals 3.81%. Meanwhile, the treatment supplemented by AHM and MN successively gave an average body composition: body water 53.52%; body protein 15.43%; body fat 12.57%; body minerals 3.83%. The results of statistical analysis showed that the administration of straw and concentrates containing C. odorata as well as AHM and MN supplementation had an unreal effect (P˃0.05) on the study composites. It was concluded that the use of AHM and vegetable oils gave the same importance to the parameters of the study.